Self-rated risk as a predictor of suicide attempts among high-risk adolescents - Rockstroh, Franziska; Reichl, Corinna; Lerch, Stefan; Fischer-Waldschmidt, Gloria; Ghinea, Denisa; Koenig, Julian; Resch, Franz; Kaess, Michael (Journal of affective disorders, 2021)
Background. Predicting suicide attempts is a challenging task for clinicians and researchers, particularly among high-risk individuals (i.e. adolescents with lifetime suicide attempts). In this study, we examined whether adolescents were able to predict their own risk of attempting suicide in the future and whether borderline personality disorder (BPD) or depressive symptoms impacted the predictive value of self-ratings. Methods. Structured clinical assessments were conducted at baseline and after 12 months in a high-risk sample of treatment-seeking adolescents (n = 134; 12-17y.; 90% female) with at least one lifetime suicide attempt. Results. During the follow-up period, n = 51 participants (38%) attempted suicide at least once. Self-rated risk was a significant predictor for the recurrence of a suicide attempt, whereas BPD and depression were not. While there was no significant interaction between self-rated risk and BPD, a negative interaction emerged between self-rated risk and depression in the prediction of a suicide attempt. Greater depression severity diminished the predictive value of self-ratings. Limitations. Depression severity was measured using a questionnaire, not a clinical interview. The findings may not be applicable to less burdened samples. Conclusions. Asking high-risk adolescents to rate their own risk of attempting suicide appears to be an easy to apply method in improving the prediction of future suicide attempts in the clinical context.
Available online 29 December 2020
Gesehen am 22.07.2021